1979
DOI: 10.1029/jb084ib14p08205
|View full text |Cite
|
Sign up to set email alerts
|

Eolian features in the western desert of Egypt and some applications to Mars

Abstract: Relations of landform types to wind regimes, bedrock composition, sediment supply, and topography are shown by field studies and satellite photographs of the Western Desert of Egypt. This desert, which lies at the core of the largest hyperarid region on earth, provides analogs of Martian wind-formed features. These include sand dunes, alternating light and dark streaks, knob 'shadows,' and yardangs. Surface particles have been segregated by wind into deposits (dunes, sand sheets, and light streaks) that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 27 publications
(4 reference statements)
1
28
0
Order By: Relevance
“…These conclusions are consistent with many previous studies of terrestrial wind streaks as possible analogs to streaks observed on other planets (e.g. Iversen, 1978, Greeley andIversen, 1985;El-Baz et al, 1979). In contrast, the botanical effects observed at the Sleeping Beauty streak will be restricted to Earth.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These conclusions are consistent with many previous studies of terrestrial wind streaks as possible analogs to streaks observed on other planets (e.g. Iversen, 1978, Greeley andIversen, 1985;El-Baz et al, 1979). In contrast, the botanical effects observed at the Sleeping Beauty streak will be restricted to Earth.…”
Section: Discussionsupporting
confidence: 81%
“…Desert pavement surfaces are prevalent, particularly in the wind streak itself, and the Amboy flow and pavements have been used in the development and confirmation of the accretionary mantle model of desert pavement development McFadden et al, 1987;Williams and Zimbelman, 1994). Cinders from the cone do not significantly contribute to the pavement in the streak Iversen, 1978, Greeley andIversen, 1987) as they do around one Egyptian wind streak described by El-Baz et al (1979). The Amboy streak owes much of its albedo contrast to the higher degree of desert pavement development in the streak caused by the cone blocking sand from traversing through the streak area, possibly enhanced sand transport via saltation over the abundant surface rocks, and by the creation of lateral winds in the lee of the cone that inhibits sand from entering the streak (Greeley and Iversen, 1985).…”
Section: Mojaue Study Sitesmentioning
confidence: 99%
“…However, in view of our results, it seems very possible to drag the sleds over wet sand with the manpower available to the Egyptians [5]. In fact, the value of the friction coefficient of wood on wood is in the range of 0.25 < μ d < 0.7 [18]; especially for the polydisperse sand here, which is closest to the Egyptian desert sand [17], we arrive at friction coefficients as low as 0.3;thus,thedraggingcan bejustas easy over sand as over the wooden sleepers. In addition, the "optimal" friction coefficient of 0.3 that we find here coincides remarkably well with estimates that have been made on the basis of the tomb drawings.…”
Section: Prl 112 175502 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…5). The Egyptians were pulling their sled through desert sand, which is very polydisperse [17] (Fig. 6).…”
mentioning
confidence: 99%
“…In Egypt, remote sensing and its applications have emerged as early as this technology was invented. Early studies were based on visual interpretation of MSS data to map sand accumulations in the Western Desert [9]. During 1980s, soil salinization was a good target to be monitored using satellite images [10].…”
Section: Introductionmentioning
confidence: 99%